Effects of diet macronutrient composition on body composition and fat distribution during weight maintenance and weight loss. (13th May 2013) - Goss, Amy M.; Goree, Laura Lee; Ellis, Amy C.; Chandler‐Laney, Paula C.; Casazza, Krista; Lockhart, Mark E.; Gower, Barbara A.
<x xml:space="preserve">Abstract</x> Objective Qualitative aspects of diet may affect body composition and propensity for weight gain or loss. We tested the hypothesis that consumption of a relatively low glycemic load (GL) diet would reduce total and visceral adipose tissue under both eucaloric and hypocaloric conditions. Design and Methods Participants were 69 healthy overweight men and women. Body composition was assessed by DXA and fat distribution by CT scan at baseline, after 8 weeks of a eucaloric diet intervention, and after 8 weeks of a hypocaloric (1000 kcal/day deficit) diet intervention. Participants were provided all food for both phases, and randomized to either a low GL diet (<45 points per 1000 kcal; n = 40) or high GL diet (>75 points per 1000 kcal, n = 29). Results After the eucaloric phase, participants who consumed the low GL diet had 11% less intra‐abdominal fat (IAAT) than those who consumed the high GL diet (P < 0.05, adjusted for total fat mass and baseline IAAT). Participants lost an average of 5.8 kg during the hypocaloric phase, with no differences in the amount of weight loss with diet assignment (P = 0.39). Following weight loss, participants who consumed the low GL diet had 4.4% less total fat mass than those who consumed the high GL diet (P < 0.05, adjusted for lean mass and baseline fat mass). Conclusions Consumption of a relatively low GL diet may affect energy partitioning, both inducing reduction in IAAT independent of weight change, and enhancing loss of fat relative to lean mass during weight loss.